Association between sedentary behaviour and socioeconomic factors, diet and lifestyle among the Balearic Islands adolescents - Bibiloni Maria del Mar; Pich Jordi; Córdova Alfredo; Pons Antoni; Tur Josep A (BMC, 2012)
Abstract Background Many different factors influenced food habits and physical activity patterns of adolescents in a complex interactive way. The aim of this study was to assess association between sedentary behaviour and socioeconomic factors, diet and lifestyle among the Balearic Islands adolescents. Methods A cross-sectional survey (n = 1961; 12-17 years old) was carried out. Physical activity was assessed using the International Physical Activity Questionnaire for adolescents (IPAQ-A). Sedentary behaviour was defined as <300 min/week of moderate and vigorous physical activity. Anthropometric measurements, body image, socio-economic and lifestyle determinants, food consumption, and adherence to the Mediterranean diet were assessed. Results The prevalence of sedentary behaviour was 37.1% (22.0% boys, 50.8% girls). Active boys consumed frequently breakfast cereals and fresh fruit; active girls yogurt, cheese, breakfast cereals, and fresh fruit; and sedentary girls high fat foods and soft drinks. Sedentary behaviour of girls was directly associated to age, and time spent on media screen and homework, and inversely related to adherence to Mediterranean diet, and body composition. Sedentary behaviour of boys was inversely related to adherence to the Mediterranean diet, and the desire to remain the same weight. Conclusions The prevalence of sedentary behaviour among Balearic Islands adolescents is high, mainly among girls. Age, sex, parental educational and profession levels, body size dissatisfaction, and poor quality diet are important factors of physical activity practice among adolescents.